1981
DOI: 10.1037/0022-0663.73.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Fluid intelligence performance in the elderly: Intraindividual variability and conditions of assessment.

Abstract: The study of performance factors plays an increasingly salient role in understanding the range of intraindividual variability (plasticity) in intellectual aging. Among performance factors considered are aspects of the testing situation. Two studies are reported that examine intraindividual variability in performance on measures of fluid intelligence (figural relations, induction), varying either practice (retesting) or testing time (standard vs. power) conditions. Subjects are elderly community residents (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
33
1

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 23 publications
10
33
1
Order By: Relevance
“…Similarly, training studies in the domain of intelligence (P. Hayslip, Maloy, & Kohl, 1995;Labouvie-Vief & Gonda, 1976) and memory (P. Baltes & Kliegl, 1992;Neely & Backman, 1995;Rebok & Balcerak, 1989;Scogin & Bienias, 1988;Yesavage, Lapp, & Sheikh, 1989) have documented the range of plasticity in intelligence and memory in older adults. In particular, it has been shown that older adults can considerably improve their cognitive functioning through systematic training (P. Hayslip et al, 1995;LabouvieVief & Conda, 1976;Neely & Backman, 1995) and even through repeated practice (Hofland, Willis, & P. Baltes, 1981). Moreover, it has been shown that in healthy, community-residing older adults normal agerelated declines in intellectual functioning can be reversed through systematic training (Schaie & Willis, 1986).…”
Section: Can Interventions Enhance Older Adults' Everyday Competence?mentioning
confidence: 99%
“…Similarly, training studies in the domain of intelligence (P. Hayslip, Maloy, & Kohl, 1995;Labouvie-Vief & Gonda, 1976) and memory (P. Baltes & Kliegl, 1992;Neely & Backman, 1995;Rebok & Balcerak, 1989;Scogin & Bienias, 1988;Yesavage, Lapp, & Sheikh, 1989) have documented the range of plasticity in intelligence and memory in older adults. In particular, it has been shown that older adults can considerably improve their cognitive functioning through systematic training (P. Hayslip et al, 1995;LabouvieVief & Conda, 1976;Neely & Backman, 1995) and even through repeated practice (Hofland, Willis, & P. Baltes, 1981). Moreover, it has been shown that in healthy, community-residing older adults normal agerelated declines in intellectual functioning can be reversed through systematic training (Schaie & Willis, 1986).…”
Section: Can Interventions Enhance Older Adults' Everyday Competence?mentioning
confidence: 99%
“…Average educational level (roughly comparable to U.S. information on educational history) was 11 years (SD = 2.7). When comparing level of intellectual performance on equivalent tests with the U.S. samples from rural Pennsylvania (e.g., Hofland et al, 1981), the Berlin sample scored about 0.5 SD higher. The Berlin sample was also slightly more heterogeneous in intellectual performance.…”
Section: Guided Instruction In Cognitive Skillsmentioning
confidence: 99%
“…To investigate this issue more systematically, Hofland, Willis, and Baltes (1981) conducted a study involving eight sessions of self-guided practice with intelligence tests. Two tests were administered, each representing one subability of fluid intelligence: figural relations and induction.…”
Section: Effects Of Retest Practice and Self-guided Learningmentioning
confidence: 99%
“…Average educational level (roughly comparable to U.S. information on educational history) was 11 years (SD = 2.7). When comparing level of intellectual performance on equivalent tests (figural relations, induction) with the U.S. samples from rural Pennsylvania (e.g., Hofland et al, 1981), the Berlin sample scored about 0.5 SD higher. In terms of interindividual variability, the Berlin sample was also slightly more heterogeneous.…”
Section: Subjectsmentioning
confidence: 99%
“…Level of difficulty and accuracy were considered for this purpose. For example, it could be that trained subjects may have improved exclusively on items that were relatively easy, or that they simply tried to answer more items than did control subjects, thereby benefitting from guessing (Hofland et al, 1981).…”
Section: Level Of Difficulty and Accuracymentioning
confidence: 99%